Answer:
(47+37)(47-37)
Step-by-step explanation:
47^2-37^2 is a difference of two squares. a^2-b^2 = (a+b)(a-b) so this expression can be factored to (47+37)(47-37) = (84)(10) = 840
That's false. Take the numbers 1, 3, and 5.
Let a = 1, b = 3, and c = 5.
ab + bc = ac
3 + 15 = 5
18 ≠ 5
Since 18 does not equal 5, this is false. If you were to use the distributive property on ab + bc = ac, you would get
b(a+c) = ac, which doesn't even make sense.
Have a nice day! :)
Answer:
C
Step-by-step explanation:
plug in the points for the equation on C and you'll get see that it fits
Answer:
22/12
Step-by-step explanation:
Answer:
the answer would be -13n-23
Step-by-step explanation:
first you want to distribute the brackets
-7(2+n) = -14-7n
+(-9-6n)
-9-6n
-14-7n-9-6n
combine the n value with an n value and an integer that doesn't have an n value
-7n-6n-14-9
= -13n-23